Advertising creativity: Its effects on interactive digital media response states towards consumers’ hierarchy of effects - Paredes, Miguel Paolo Lucero (Animo Repository, 2023)
The study focuses on the influence of Advertising Creativity (AC) on advertising effectiveness in the context of emerging dynamic characteristics of Interactive Digital Media (IDM). This investigation extends the process of Advertising Creativity reception towards the different stages of the Hierarchy of Effects (HOE) to include Conditional Media Effects and Media Response States. PLS-SEM was utilized as the primary statistical tool to analyze the various relationships to address the research goals. It was uncovered that Advertising Creativity effects occur through engaging immediate responses at the time of exposure of consumers to ad stimuli further significantly having positive influence on all HOE stages. The strengths of these effects vary with HOE stages that revolve around immediate responses such as awareness, learning, and memory, as well as brand liking having more resounding practical implications as compared to more rationally involved HOE stages such as that of accepting or rejecting ad claims and brand intentions. As advertising, by its very nature is designed to disrupt the original motivations and activities of audiences when going about tasks, the study posits that upon the presentation of new stimuli in the form of advertising creativity, the media response is immediate toward the stimuli at hand. This point of engagement enables advertisers to capture attention and interest to communicate brand messages in the service of client goals. The study provides a practical view of AC’s benefits to specific HOE stages enabling advertisers to develop strategies given the value and limitations of AC within integrated marketing campaigns. As creativity suffers when we fall into formulaic thinking and assumptions, constant investigation of AC as a component of advertising effectiveness keeps us abreast with dynamic consumer processing of advertising communications constantly developing in line with emerging media technology. Keywords: advertising creativity, DSMM, the hierarchy of effects, conditional media effects, media response states